2018
DOI: 10.1007/s00467-018-3905-7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, morbidity, and therapy of hepatitis E virus infection in pediatric renal allograft recipients

Abstract: Given an HEV seroprevalence of 13.3% in pediatric renal transplant recipients and an HEV viremia of 4.4%, HEV infection should be considered in patients with otherwise unexplained elevation of liver enzymes. HEV infection does not necessarily respond to reduction of immunosuppressive therapy, but can be effectively and safely treated with ribavirin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Twenty‐one studies described the effect of reduction of immunosuppressive medication, representing a total of 174 patients 22‐40 . In most patients (67%), the reduced drug was not described.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty‐one studies described the effect of reduction of immunosuppressive medication, representing a total of 174 patients 22‐40 . In most patients (67%), the reduced drug was not described.…”
Section: Resultsmentioning
confidence: 99%
“…Treatment effect of RBV was described in 34 studies 22,23,25‐27,32,34‐36,38‐62 . The majority of the 395 patients treated with RBV was male, and almost all patients were SOT recipients.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, this result should be taken with caution. First, other studies or case reports showed a failure of viral clearance after immunosuppressive dose reduction [17][18][19][20][21]. Second, the elapsed time between the initiation of immunosuppression reduction and the time of self-resolution could be as high as or more than 1 year [11,14].…”
Section: Discussionmentioning
confidence: 99%
“…One pediatric patient developed HEV-induced liver cirrhosis after hematological stem cell transplantation ( Halac et al, 2012a ). In an isolated cohort study of 90 pediatric renal allograft recipients had 13.3%, (12/90) HEV IgG positivity with 4.4% (4/90) recipients had HEV genotype-3 active replication and further leading to chronicity ( Cordts et al, 2018 ). Thus from the available world literature, it is evident that children less frequently get affected with HEV and seldom develop chronicity.…”
Section: Hev Infection and Chronicity In Pediatric And Young Populatimentioning
confidence: 99%